Continuing the Conversation on Collegiality - Angela Walters; Stacey Smith; Melissa Hunsicker-Walburn; Brooke Moore (Academic Chairpersons Conference Proceedings, 2020)
Are you interested in measuring and incentivizing collegiality? Do you have concerns with using collegiality for faculty development, merit, or tenure? Bring your experiences and perspectives to the table as three department chairs and their college dean (a lawyer) facilitate a healthy discussion on the measurement tools, legal landscape, and business case for collegiality.
Keywords: Collegiality; Higher Education; Faculty Development; Civility; Assessment; Merit